Testbed Helsinki / EdTech (Testbed Helsinki)
EdTech company, join us and kick-start your development activities! We enable the development and testing of smart innovations in Helsinki’s primary schools, upper secondary schools, and other learning environments.
KerkoCite.ItemAlsoKnownAs: 2129771:GSE4WH7R